Land Heterogeneity, Agricultural Income Forgone and Environmental Benefit: An Assessment of Incentive Compatibility Problems in Environmental Stewardship Schemes - Fraser,RW (2008)
This paper examines the issue of incentive-compatibility within environmental stewardship schemes where incentive payments to farmers to provide environmental goods and services are based on foregone agricultural income. The particular focus of the paper is on the role of land heterogeneity, whether in terms of agricultural value or environmental value, in leading to divergences between the actual and the socially optimal level of provision of environmental goods and services. It is shown that such goods and services are systematically over or under-provided depending on the characteristics of land heterogeneity both within and between landscape regions. It is therefore concluded that incentive payments should be based on social willingness-to pay for the provision of environmental goods and services.